Association of galactose and insulin resistance in polycystic ovary syndrome: A case-control study. (May 2022) - Na, Zhijing; Jiang, Hongyu; Meng, Yaxin; Song, Jiahui; Feng, Di; Fang, Yuanyuan; Shi, Bei; Li, Da
Summary: Background: Polycystic ovary syndrome (PCOS) is closely linked to metabolic disorders. Recent reports have identified galactose as having strong associations with metabolic disorders, however, the correlation between galactose and PCOS remains largely unknown. Methods: The serum galactose levels of 104 patients with PCOS and 98 controls were measured, and their relationships with several metabolic parameters were analyzed. The study took place at the Center for Reproductive Medicine at Shengjing Hospital of China Medical University, Shenyang, China from July 13 to Oct 20, 2020. The relationships between serum galactose and PCOS as well as PCOS-related insulin resistance were investigated via logistic regression analyses, and the performance of serum galactose as a potential biomarker for PCOS was evaluated using receiver operating characteristic curve analysis. Findings: Higher serum galactose levels were observed in the patients with PCOS than in the controls ( p  = 0.001). There was still a correlation between circulating galactose levels and PCOS after adjusting for covariates ( p  = 0.002; odds ratio (OR), 1.133; 95% confidence interval (CI) 1.047–1.227). Serum galactose levels were shown to be most closely related to the fasting serum insulin level ( r  = 0.370, p  = 0.001) and were higher in the insulin-resistant subgroup than in the non-insulin-resistant subgroup of patients with PCOS ( p  = 0.001). There was no difference in serum galactose levels between the insulin-resistant and non-insulin-resistant subgroups of women in the control group ( p  > 0.05). Furthermore, higher serum galactose levels were shown to be associated with insulin resistance in PCOS ( p  = 0.004; OR, 26.017; 95% CI, 2.907–232.810). The area under the curve for galactose-mediated prediction of PCOS was 80.0%, with a sensitivity of 71.0% and a specificity of 86.4%. Interpretation: Higher circulating galactose levels correlate with PCOS and PCOS-related insulin resistance; therefore, it may serve as a potential biomarker for patients with PCOS. These findings require further validation in a study with a larger sample size. Funding: National Natural Science Foundation of China (No. 82, 071, 607 and 32, 100, 691); LiaoNing Revitalization Talents Program (No. XLYC1907071); Fok Ying Tung Education Foundation (No. 151, 039); Key Research and Development Program of Liaoning Province (NO. 2, 018, 225, 062); Outstanding Scientific Fund of Shengjing Hospital (No. 202, 003).